Increase of Vascular Endothelial Growth Factor and Decrease of MCP-1 and Some Updated Epidemiology Aspects of Cystic Echinococcosis Human Cases in Calabria Region - Matera, Giovanni; Loria, Maria Teresa; Peronace, Cinzia; Catanzariti, Tatiana; Settembre, Pio; Giancotti, Aida; Lamberti, Angelo G.; Barreca, Giorgio S.; Galati, Luisa; Dodaro, Gessica; Mazzitelli, Maria; Strazzulla, Alessio; et al. (Mediators of Inflammation, 2018)
We aim to investigate some of the pathogenetic mediators of the human echinococcosis and to obtain updated epidemiological findings on cases of echinococcosis in Calabria, Southern Italy. Echinococcosis diagnosis was based on imaging, serological investigations, and molecular assay. Indeed, real-time PCR indicated the presence of G2/G3 genotypes of Echinococcus granulosus complex. Regarding pathogenesis, a relevant novel tool of immune depression should be deemed the reduced level of serum MCP-1. Also, we found a previously unreported VEGF, possibly associated with neovascularization requested by the parasite cyst metabolism. Cytokine profiles suggest a bias of the immunity toward Th2 and Treg responses. Nitric oxide levels exhibited a significant decrease one week after therapy versus basal level measured before surgery and/or chemotherapy. An increase of serum total IgE class and IgG4 subclass was found in Echinococcus-positive patients versus controls. Our data demonstrated an endemic spreading, at least in the province of Catanzaro and neighboring Calabria territories, for such parasitosis with the novel issue of the number of female overcoming male cases. In conclusion, the novel findings of this study were the increased VEGF and the reduced serum MCP-1 in the studied cases, as well as the number of Echinococcus-infected females overcoming the infected males.